Produktivitas Entok Betina dengan Pemberian Pakan Terbatas Selama Periode Pertumbuhan - Ayuningtyas, G.; Jakaria, Jakaria; Rukmiasih, Rukmiasih; Budiman, C. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
The objective of this research was to study the effect of restricted feeding on muscovy duck performance’s in grower period, the development of reproduction organ, puberty characteristic, egg production, and blood lavel of cholesterol and trigliseride. Total 32 of female muscovy duck , 8-22 weeks age ware evaluated in this research. A completely randomized design with 3 level treatments were used to arrange the treatments. The treatments of restricted feeding were ad libitum consumption ( P1); 70% ad libitum (P2) and 40 % ad libitum (P3). The diet contain 22% crude protein (0-3 weeks age), 18% crude protein (4-7 weeks age), and 14% crude protein (8-22 weeks age). The parameters observed were: performance’s in grower period (feed consumption, body weight, total daily gain), puberty characteristic (puberty age, body weight on puberty, first egg weight), egg production on first cycle, the development of reproduction organ, and blood lavel of cholesterol and trigliseride. The results showed that body weight of muscovy duck P2 and P3 lower then P1. The restricted feeding could delayed development of folicle ovary and age puberty. The blood level of cholesterol’s muscovy duck P2 and P3 lower then moscovy duck P1.